Eimeria tenella aspartyl protease is identified as a potential TLR15 ligand and activates macrophages and dendritic cells in chickens - Chen Chen; Zhichao Men; Xianglin Pu; Mingmin Lu; Lixin Xu; Ruofeng Yan; Xiangrui Li; Xiaokai Song (Poultry Science, 2025)
Toll-like receptor (TLR)-mediated recognition of specific ligands is critical for initiating innate immunity against Eimeria infections. However, the avian-specific TLR15 has unclear immunological functions, including its specific ligands and role in anti-coccidia immunity. In this study, an aspartyl protease from Eimeria tenella (EteASP) was identified as a potential TLR15 ligand by co-immunoprecipitation. Two distinct TLR15-expressing innate immune cell populations, macrophages and dendritic cells, were employed as models to investigate the immune responses triggered by recombinant EteASP protein (rEteASP). In macrophages, rEteASP induced robust immune activation, associated with the stimulation of both NF-κB and MAPK pathways. This activation correlated with increased production of pro-inflammatory cytokines (IL-1β, IL-6, TNF-α), nitric oxide, and reactive oxygen species, alongside enhanced phagocytosis. Furthermore, rEteASP promoted classical dendritic cell activation in chicken bone marrow-derived dendritic cells, marked by stellate morphology and upregulated CD11c and MHC II surface expression. The activation patterns in chBMDCs mirrored those in macrophages, characterized by increased production of immune mediators. A mixed lymphocyte reaction (MLR) further demonstrated that rEteASP-activated dendritic cells efficiently triggered naive T cell activation, driving a shift towards balanced Th1/Th2-type cellular immune response. Collectively, these findings establish EteASP as a potent immunomodulator capable of activating key innate immune effector functions in macrophages and dendritic cells, and bridging to adaptive immunity. Our data implicate TLR15 as a potential receptor contributing to these responses, broadening the investigation of TLR15 ligands in protozoa and offering novel insights into Eimeria-host immune interactions. However, the potential involvement of additional pattern recognition receptors in EteASP recognition and the definitive role of TLR15 requires further investigation.